The Role of HWDI (Indonesian Association of Women with Disabilities) in Increasing the Self Confidence of Persons with Disabilities in Sukarame Bandar Lampung - Nasution, Sri Ilham; Dahlia, Livia Cici (Universitas Islam Negeri Raden Intan Lampung, 2021)
This article examines the role of HWDI (Indonesian Women with Disabilities Association) in increasing the confidence of people with disabilities in Sukarame Bandar Lampung, where women with disabilities always feel inferior, have low self-esteem, do not have confidence when socializing and are in the midst of society. This paper aims to increase the self-confidence of people with disabilities using group guidance techniques. This research was conducted at HWDI (Indonesian Women with Disabilities Association) Sukarame Bandar Lampung. This research data collection using interviews, observation and documentation with the Snowball sampling technique. Data analysis in this study used descriptive qualitative data validity by means of triangulation and so on. The results of this paper indicate that the process of implementing group guidance for women with disabilities in HWDI is carried out in four stages: the first stage is the formation, the second is the transition, the third is the activity and the fourth is the termination using the Humanistic approach. These four stages can increase the confidence of women with disabilities at HWDI (Indonesian Disabled Women Association) Sukarame Bandar Lampung